2018
DOI: 10.3758/s13428-018-1019-6
|View full text |Cite
|
Sign up to set email alerts
|

Gulf Arabic nouns and verbs: A standardized set of 319 object pictures and 141 action pictures, with predictors of naming latencies

Abstract: Standardized pictorial stimuli and predictors of successful picture naming are not readily available for Gulf Arabic. On the basis of data obtained from Qatari Arabic, a variety of Gulf Arabic, the present study provides norms for a set of 319 object pictures and a set of 141 action pictures. Norms were collected from healthy speakers, using a picture-naming paradigm and rating tasks. Norms for naming latencies, name agreement, visual complexity, image agreement, imageability, age of acquisition, and familiari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 73 publications
6
47
0
Order By: Relevance
“…It is reported that words with high familiarity are processed faster than their counterparts (Boukadi et al, 2016;Akinina et al, 2014;Barca, Burani, & Arduino, 2002). This variable has been found to influence lexical retrieval as reported in Levantine Arabic (Khwaileh et al, 2014), Gulf Arabic (Khwaileh et al 2018) and Tunisian Arabic (Boukadi et al, 2016). Familiarity can be measured through a five-point rating scale ("1" indicating very unfamiliar; "5" indicating very familiar).…”
Section: Factors Influencing Word Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…It is reported that words with high familiarity are processed faster than their counterparts (Boukadi et al, 2016;Akinina et al, 2014;Barca, Burani, & Arduino, 2002). This variable has been found to influence lexical retrieval as reported in Levantine Arabic (Khwaileh et al, 2014), Gulf Arabic (Khwaileh et al 2018) and Tunisian Arabic (Boukadi et al, 2016). Familiarity can be measured through a five-point rating scale ("1" indicating very unfamiliar; "5" indicating very familiar).…”
Section: Factors Influencing Word Processingmentioning
confidence: 99%
“…According to Khwaileh et al (2018), word frequency can be measured through extracting frequency values from corpora, such as in Khwaileh et al (2018), or through rating tasks as done by Boukadi, Zouaidi & Wilson (2016), where participants rated the frequency of 348 words using a seven-point scale, "1" indicating the word is never encountered and "7" indicating that it is encountered several times a day. Khwaileh et al (2018) define the 'age of acquisition' as the age at which a given word is learned. They further state that words learned at an earlier age are processed faster and more accurately than later acquired ones (e.g.…”
Section: Factors Influencing Word Processingmentioning
confidence: 99%
See 3 more Smart Citations